JOINING EFFORTS OF EMPLOYERS AND EDUCATIONAL INSTITUTIONS TO DEVELOP COMPETENT GRADUATES - Zupan, Nada; Eftimov, Lјupcho; Jovanovska, Katerina; Petrovski, Darko (University of Dubrovnik, 2016)
Youth unemployment remains unacceptably high in Europe. Despite increasing numbers of well-educated graduates, employers often report difficulties in recruiting skilled young workforce. The prevailing view is also that education institutions are slow to respond to the needs of business community and do not sufficiently incorporate skills development into curricula. The reason for this mismatch might be found in the failure of three stakeholders (employers, students and education institutions) to mutually understand their needs; they often operate in "parallel universes". Research shows that young workforce especially lacks sufficient portfolio of soft skills. Thus the aim of our study is to identify gaps in competencies developed through education and those required by employers. We researched the situation in the Republic of Macedonia and examined students’, professors’ and employers' perceptions of the importance of soft skills and their development through the university education. Our results suggest students are not sufficiently aware of the importance of soft skills relative to professors and employers. Also, university education programs despite reforms in the last decade fail to provide the development of soft skills needed by employers in their graduates. We end with the discussion and proposals on how to close the existing gaps, focusing on a closer collaboration between education providers and employers in order to improve youth competencies and employability.
Keywords: employability, soft skills, university graduates, Republic of Macedonia